Development of the positive engagement continuously variable transmission design with the application of graph theory - Ivanov, Viktor; Urum, Galyna; Ivanova, Svitlana; Volkova, Mariia (Eastern-European Journal of Enterprise Technologies, 2018)
Various designs of CVTs were explored from two points of view: analysis of the design itself and analysis of the methods and techniques, used in the process of creation of the CVT. To solve the problem of finding new designs of mechanisms, the graph transformation method was developed. It includes the following heuristic techniques: a decrease in the number of graph nodes at simplification of a design or to remove non-essential elements; a change in location of graph edges and comparison of a new location of edges and necessary changes in a design; a search for all possible options for location of the parts that correspond to the same graph; introduction to the graph of the nodes, corresponding to the property, for implementation of which a part (a node) can be added to a design or, vice versa, can be removed from a design, and the property it implemented will be implemented by other parts. The original design of the CVT, in which load is transmitted by gear engagement without using friction disks and flexible sections, was developed. A continuously variable of transition ratio is ensured by a gear wheel with a variable pitch. The gear wheel consists of three gear sectors, two of which are involved in meshing. The third unloaded sector performs a turn with angular velocity that is higher than velocity of rotation of the output shaft until it takes a position before coming into engagement. The CVT does not have such drawback as fluctuations of transmission ratio. Based on the analysis of the bond-graphs, efficiency was determined, which depending on velocity of the output shaft is in the range of 95…97 %. The disadvantage of the developed design is an insufficiently wide gear ratio range R=1.5…1.6, which is limited by transverse contact ratio εα